ISLAM PROGRESIF INDONESIA: TELAAH PEMIKIRAN DAN GERAKAN JARINGAN ISLAM LIBERAL (JIL) - A. ILYAS ISMAIL (Al Qalam, 2019)
Theofogicaffy, Islam is one and absolutely correct. However, historicaffy, after being understood and translated into the real life, Islam is not single, but various or plural that manifests at feast in three schools of thoughts: Traditional Islam, Revivalist Islam (fundamentalism), and Liberal Islam (Progressive). The group of Jaringan Islam Liberal (JIL) represents the fast school of thoughts. Even though it is stiff young (ten years), JIL becomes populer because it frequentfy proposes the new thoughts that often evoke controversions in the community. The reformation of thoughts proposed by JIL covers four areas: first, reformation in politics. In this context, JIL gives a priority to the idea of secularism; Second, reformation in socio-religion. Dealing with this, JIL proposes the concept of pluralism; Third, reformation in individual freedom. In this case, JIL gives a priority to the idea of liberalism both in thoughts and actions;fourth, reformation in women. Regarding this, JIL proposes the idea of gender equaliry. This reformation thought of JIL receives pro and con in the community. On the one hand,some of them panne and fulminate it; on the other hand, the other ones support and give appreciation. In such situation, JIL grows as a thought and Islamic progressive movement in Indonesia. Key Words: Islamic Thought, JIL, Secularism, Pluralism, Liberalism, and Gender Equality.